Proposed legal reforms to protect South Africa's informal social security - Zeelie, Robin Erin (University of Pretoria, 2024)
Informal social security is a non-governmental form of social security between kin and/or community members and is a prevalent practice in South Africa. The question this dissertation analyses is whether the South African government fails in its constitutional duty to protect and advance informal social security. The dissertation limits itself to analysing cash transfers through social grants, and social insurance in the Unemployment Insurance Act and the Compensation for Occupational Injuries and Diseases Act. This dissertation delineates its definition of informal social security, historically contextualises its practice, and explains the contemporary formal social security framework. This dissertation finds five prominent shortcomings in the formal framework, and that these shortcomings have a profoundly negative, weakening effect on informal social security, as the more people who rely on informal mechanisms, the less it can respond to needs arising from life contingencies, shocks, and risks. The dissertation concludes by analysing three legal reform proposals the state can implement: extending existing social insurance frameworks to those in the informal sector, promoting cooperatives as a formal platform for the informal, and the basic income grant.
Keywords: Basic income grant; Cooperatives; Duty; History; Informal social security; Republic of South Africa; Social assistance; Social security

Compliance with decent work standards by multinational enterprises - Maluleke, Tirhani Foster (University of Pretoria, 2024)
In contemporary times, the issue of human and labour rights violations has gained significant momentum, rendering it imperative for international organisations, states, and businesses to address this critical concern. It is widely acknowledged that while multinational enterprises can aid in achieving economic growth by investing directly overseas and raising the standard of living for the residents of host nations, their business operations may also result in abuse of human and labour rights. The United Nations (UN) Charter was drafted to set forth obligations for individual states, yet businesses do not bear international legal obligations. The Universal Declaration on Human Rights was adopted to implement the substantive contents of human rights referred to in the UN Charter in the general way. The preamble of the Universal Declaration refers to all organs of society, but, at the time of its adoption, businesses were not considered among such organs. It was inconceivable that business organisations would become so economically powerful within a few decades that they would pose a significant risk to human and labour rights, which would not be easily regulated under the national law of their host nations. It is the hypothesis of this study that numerous multinational enterprises (MNEs) violate core human and core labour rights, and that the existing regulatory framework does not adequately regulate them. To prove this hypothesis, this thesis will adopt a two phased approach. Firstly, a careful case law and literature review will reveal the inadequate regulation of MNEs. Evidence suggests that MNEs are guilty of flagrant labour standards and human rights violations. As a result of globalisation, MNEs have gained stronger international influence, and they are able to move their businesses to countries with low cost of labour and less regulations. This phenomenon weakens the governments of host nations as they are keen to promote foreign direct investment in order to reduce unemployment and to ensure economic growth. As a result, the host nations are encouraged to set laws that will attract MNEs at the expense of human and core labour rights. As result, MNEs are not held accountable in respect of their violation of human and labour rights. Secondly, this thesis will assess the efficacy of the regulatory instruments developed by the international community in response to the mentioned problem. This aspect is covered in Chapter 3 to 7 of this thesis. The strategies include the public and private hard law and soft law mechanisms developed at international level as well as campaigns by Non-Governmental Organisations (NGOs). Based on evidence, this thesis will conclude that a soft law approach is not fully effective. As such, Chapter 8 of this thesis proposes the introduction of some hard law measures to improve the existing soft law instruments to augment the existing legislative frameworks of the host countries. In particular, the thesis recommends regulatory reforms, which will empower the International Labour Organisation to intervene to prevent the labour rights violations by MNEs and where such violations occur, to at least provide effective remedies to vulnerable employees. This thesis constitutes a theoretical study, which attempts to provide suggestions regarding the implementation of realistic measures, which if implemented, may contribute to the attainment of decent work for all men and women who are engaged in work for MNEs.
Keywords: Codes of conduct; Decent work; Hard law; Human rights; Human rights due diligence; ILO MNE declaration; International Labour Organisation; International framework agreements; Labour rights; Multinational enterprises; OECD guidelines; Regional free trade agreements; Soft law

Employee’s Pilferage and Security in Beverage Manufacturing Companies in Lagos State, Nigeria - Attah, Edwin; Abdullahi, Liman; Yusuf, Usman (African Journal of Politics and Administrative Studies, 2024)
The purpose of this paper is to examine the relationship between employee pilferage of pilferage and security in beverage manufacturing companies in Lagos State. The study is anchored on the rational choice theory in order to understand the connection between pilferage and security in beverage manufacturing companies in Lagos State. The researcher adopted a mixed research method involving survey research and historical research designs. The population of this study is 8,595 staff. This comprises all employees of Promasidor Nigeria Ltd, Nigeria Bottling Company (Coca Cola), Cadbury Nigeria Plc, and Guiness Nigeria Plc. The sample size of the study was 400 determined using Rakesh Sample size formula. Data were collected from primary and secondary sources. Primary data were collected using questionnaires, while secondary data were collected from related works on pilferage and security in beverage manufacturing companies. Data collected from questionnaire were analyzed using absolute frequencies and simple percentages, while data from secondary sources were analyzed using relational-content analysis. Among other things, it was found that the higher the level of pilferage, the lower the level of security of employees in beverage manufacturing companies in Lagos State. Among other things, it was recommended that given that there is relationship between pilferage and security in beverage manufacturing companies in Lagos State, beverage manufacturing companies in the state should ensure that stealing is drastically reduced in their various organizations through employment, training and proper motivation of staff who must be full-time staff. This would largely make the employees committed to work and shun pilferage.
Keywords: Pilferage; companies; employee; manufacturing; security

A comparative legal analysis of the accommodation of neurodiversity in the workplace : towards a universal right to reasonable accommodation - Conradie, Riana (Stellenbosch University, 2024)
Workforces are made up of individuals with differences in personal characteristics, differences that may be traced back to unique personality types and traits and – sometimes – neurodivergence. Due to the inherent subjectivity of the interpersonal relationships that form the foundation of a work environment, these differences in personal characteristics inevitably lead to tension. In addition, as part of managing a work environment employers frequently take decisions that may be influenced by views and perceptions regarding employees’ personal characteristics. This study starts with a descriptive examination of the meaning of personality and the influence that personality traits and types may have on employment. This is followed by a descriptive examination of neurodivergence, the various forms of neurodivergence, and the impact of these conditions on the work environment. Building on these descriptive and conceptual underpinnings, the legal implications of neurodiversity in the workplace are investigated by identifying which principles of the existing South African employment law framework may be utilised to provide protection and promote respect for neurodiversity and the neurodiverse differences between employees. This encompasses a discussion of the South African employment law rules relating to recruitment and selection of employees, some of the rules applicable to the day-to-day management of employees, and the rules relating to termination of employment that may be (in)directly influenced by considerations of neurodiversity. The focus thereafter shifts to consider the legal principles of employment discrimination law, where it is found that the listed ground of disability and an unlisted arbitrary ground may potentially be used as the applicable grounds of discrimination by employees if they are prejudiced due to their neurodiverse characteristics. In addition, the possibility that the rules on reasonable accommodation may be utilised as primary mechanism to properly regulate neurodiversity in the work environment and protect against prejudicial treatment of employees due to their inherent personal neurodiverse characteristics is also considered. The South African position and potential employment law rules that may apply to the management of neurodiversity in the work environment is compared to the position in the United Kingdom by focusing on the meaning of disability, the right to reasonable adjustments, and the right to request flexible working arrangements. Finally, the conclusions that may be drawn from this study are emphasised and are followed by some recommendations on how (reasonable) accommodation of neurodiversity in the work environment may appropriately be used as primary mechanism to provide employees with sufficient and appropriate protection of differences in neurodiverse characteristics. Even though this study focuses on neurodiversity and neurological differences between employees, the principles and recommendations from this study may be of value in relation to the appropriate management and regulation of all inherent differences between employees.
Keywords: Discrimination in employment; Diversity in the workplace; Employment; Labor laws and legislation; Neurodivergent people; Neurodiversity; People with disabilities

The legitimacy of dismissals for off-duty misconduct in South African labour law - Phulu, Thandekile (University of Pretoria, 2024)
The main aim of this thesis is to solve the uncertainties brought about by dismissals for off-duty misconduct. First, it should be acknowledged that the world as we know it has changed and continues to evolve. Dismissals have been significantly impacted by the use of social media outside the workplace. The legalisation of the use of cannabis by an adult person has also brought uncertainties in the way dismissals are handled, especially in cases where an employee consumes cannabis off-duty. These two aspects have significantly influenced dismissals for off-duty misconduct in South Africa, with employees alleging that their rights to privacy, dignity and freedom of expression are infringed. The thesis reveals that regardless of these modern changes, off-duty misconduct dismissal is still governed by the generic provisions of the Labour Relations Act 1995 and its Code of Good Practice: Dismissal. The thesis underscores the lack of clarity regarding the regulation of dismissals for off-duty misconduct in South Africa. Furthermore, despite the judiciary’s establishment of tests (the nexus test and the breakdown of the employment relationship), challenges in adjudicating off-duty misconduct cases persist. This thesis analyses the South African legal framework governing dismissals for off-duty misconduct. The research investigates the evolution of South African dismissal law, tracing its development from the pre-democratic era to the post-democratic era. This investigation scrutinises the shifts in the legal landscape regarding dismissals for off-duty misconduct. The analysis encompasses a range of legal instruments pertinent to South Africa, including legislation, international law, common law, and judicial precedent. The current need for a Code of Good Practice for off-duty misconduct dismissal is highlighted. This rationale is prompted by a comparative examination of other countries where, despite the absence of specific codes addressing off-duty misconduct, a proactive stance has been adopted to safeguard employees’ off-duty rights by enacting relevant legislation. These chosen states have statutes regulating employees’ off-duty conduct and clarifying which conduct is protected and in which circumstances. Consequently, the thesis proposes a Code of Good Practice: Dismissal for Off-duty Misconduct. This Code would assist in the uniformity of application of relevant aspects in determining the fairness of dismissals for off-duty misconduct, thus alleviating labour suits concerning this type of dismissal. The Code would also provide employers with guidelines on how to draft off-duty misconduct policies without infringing employees’ constitutional rights.
URI: https://repository.up.ac.za/handle/2263/97021
Keywords: Cannabis use; Dismissal; Labour law; Misconduct; Off-duty; Social media; South Africa

The Influence of Corporate Sustainability Laws on Multi-Stakeholder Initiatives to Eliminate Forced and Child Labour in Supply Chains - Fanou, Temisan (McMaster University, 2024)
An array of governance initiatives has emerged to address forced labour and labour exploitation in global value chains (GVCs). Drawing on the transnational business governance interactions theoretical framework, as well as Timothy Bartley’s place-conscious transnational governance model, this thesis examines the interaction between two of these hybrid forms of governance: multi-stakeholder initiatives and corporate sustainability laws. I conduct a case study of the cocoa sector, and specifically of the multinational company, Nestlé, using multiple qualitative research methods including legal analysis, key informant interviews, and documentary analysis. My research suggests that the layering of corporate sustainability laws, and particularly the French Duty of Vigilance Law, on top of CSR and MSIs in the cocoa sector, is not addressing the governance gap that permits corporations to evade accountability for human rights abuses in their supply chain. I find that the introduction of corporate sustainability laws may have contributed to a decrease in Nestlé's efforts to address labor violations in certain areas, while in others, it appears to have supported the continuation of existing practices. This raises implications for the continuous efforts in various jurisdictions to introduce these laws as a solution to the shortcomings of private, voluntary rule-making systems. Further research is required to explore how these governance mechanisms are interacting in other sectors, in companies of different sizes, and within various types of MSIs. This will help identify the factors that influence interactions and shed further light on the path forward for policymakers.

Antitrust policy and EU labour markets : lessons from the US and comparative prospects - Langlois D'estaintot, Isaure (European University Institute, 2024)
Recent empirical evidence suggests that labour markets are not as competitive as previously thought. In that context, mobilizing antitrust policy has been discussed as a possible solution. The proposition sounds counterintuitive, however. If workers are paid below the competitive level, doesn’t this promote consumers’ outcomes by reducing downstream prices? Given that antitrust policy promotes consumer welfare, why would antitrust authorities intervene against such a state of affairs? Besides, why would stepping up on antitrust enforcement improve workers’ outcomes? Their interests have traditionally been protected through their exclusion from the scope of antitrust enforcement, not by the enforcement of antitrust rules to their benefit. This thesis demonstrates that those spontaneous assumptions do not hold. Consumer welfare does not speak against the defence of workers’ interests. First, the focus on consumers is a by product of methods: it does not prevent consideration of other types of market participants. Moreover, consumers benefit from competitive labour markets. The welfare effects of monopsony power simultaneously worsen workers and consumers’ outcomes. As for the promotion of workers’ interests, it can be achieved through both positive and negative enforcement of antitrust. So far, the EU Commission has been less proactive than the American DOJ and FTC on the issue of antitrust enforcement in labour markets ( although the state of affairs is evolving). While this difference may stem from EU workers benefitting from higher levels of social protection than US workers, those higher levels of protection may not negate the usefulness of antitrust ’s intervention. The low levels of antitrust enforcement in EU labour markets may result from legal uncertainty and case law inconsistency more than an absence of harm. Just like the merger control apparatus, Article 101 and 102 TFEU can be used to scrutinize labour markets. While doing so involves some practical complexities, they can be overcome.
Accepted: 2024-04-08T07:03:10Z
Keywords: Antitrust law; European Union countries; Labor laws and legislation; Unfair competition